2008
DOI: 10.1007/s10658-008-9379-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of novel Fusarium graminearum microsatellite markers in different Fusarium species from various countries

Abstract: Fifteen novel microsatellite markers were isolated from Fusarium graminearum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
1
17
0
1
Order By: Relevance
“…Beauveria Clade C, for which they were not designed. These data correspond to those of previous studies reporting limited cross taxa amplification of SSR markers in fungi as compared to animals and plants ( Barbara et al, 2007;Vogelgsang et al, 2009). Similar to this study, loci that could be amplified across taxa showed no or only low levels of polymorphism suggesting that transfer of SSR markers among fungal species may generally be limited.…”
Section: Discussionsupporting
confidence: 91%
“…Beauveria Clade C, for which they were not designed. These data correspond to those of previous studies reporting limited cross taxa amplification of SSR markers in fungi as compared to animals and plants ( Barbara et al, 2007;Vogelgsang et al, 2009). Similar to this study, loci that could be amplified across taxa showed no or only low levels of polymorphism suggesting that transfer of SSR markers among fungal species may generally be limited.…”
Section: Discussionsupporting
confidence: 91%
“…Several molecular markers have been used to analyse the diversity of Fusarium plant pathogens at the genome level: amplified fragment length polymorphism (AFLP) in F. graminearum and F. asiaticum O'Donell, Aoki, Kistler & Geiser (Qu et al 2008), random amplified polymorphic DNA (RAPD) in F. graminearum and F. poae (Ouellet and Seifert 1993;Kerényi et al 1997), simple sequence repeats (SSR) in F. graminearum and F. culmorum (Vogelgsang et al 2009), and inter-simple sequence repeats (ISSR) in F. graminearum and F. culmorum (Mishra et al 2003(Mishra et al , 2004. AFLP analysis has been used also for studying relationships at taxonomic levels within a world-wide collection of F. sporotrichioides Sherbakoff, F. langsethiae Torp & Nirenberg and F. poae isolates (Schmidt et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of the selected primers to produce species‐specific fingerprints was apparent. Fifteen novel microsatellite markers were isolated from Fusarium graminearum (Vogelgsang et al . 2009).…”
Section: Resultsmentioning
confidence: 99%